Lateralizacja funkcji językowych u pacjentów z pierwotnymi nowotworami OUN. Lokalizacja pierwotnie rozproszona, transfer międzypółkulowy, czy różnice interpersonalne - Rożek, Agnieszka (Logopedia Silesiana, 2015)
There are still many controversies concerning the location of cortical functional areas involved in speech processes. It has been proved that brain plasticity mechanisms enable the transfer of functions between areas located in the same hemisphere as well as through the commissural fibres system to the opposite hemisphere. The originally distributed location of functional areas may also exist simultaneously in both hemispheres. The aim of this study was twofold: to analyse speech problems occurring in patients treated for primary tumours of the CNS and to attempt to correlate symptoms with the location of damage. The Montreal Cognitive Assessment (MoCA), The Right Hemisphere Language Battery – Polish version (RHLB-PL) and the neurologopaedic diagnosis were used for evaluation. The authors present the preliminary results of a group of twenty patients with primary brain tumours.